2016
DOI: 10.1159/000447865
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of Suicidal Erythrocyte Death by Fascaplysin

Abstract: Background/Aims: The bis-indole alkaloid Fascaplysin is effective against malignancy, an effect at least partially due to stimulation of tumor cell apoptosis. Similar to apoptosis of nucleated cells, erythrocytes could enter suicidal erythrocyte death or eryptosis, characterized by cell shrinkage and cell membrane scrambling with phosphatidylserine translocation to the erythrocyte surface. Triggers of eryptosis include increase of cytosolic Ca2+ activity ([Ca2+]i), oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…In addition to the cell alteration, the deformation of the mice erythrocytes can be linked to the cell physical alteration (Yoon and You, 2016) and the existence of eryptosis, suicidal death erythrocytes (Mischitelli et al, 2016). Consistent with this assessment, we found that deformation level, as well as the deformed erythrocytes, were significantly increased in the mice exposed to the ultrafine particles.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to the cell alteration, the deformation of the mice erythrocytes can be linked to the cell physical alteration (Yoon and You, 2016) and the existence of eryptosis, suicidal death erythrocytes (Mischitelli et al, 2016). Consistent with this assessment, we found that deformation level, as well as the deformed erythrocytes, were significantly increased in the mice exposed to the ultrafine particles.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with this result, erythrocytes are highly deformable and may also exhibit reduced deformability and stronger aggregation in many pathological situations, such as sickle cell anemia (Popel and Johnson, 2005). Eryptosis itself can be triggered by any kind of erythrocyte injury, including oxidative stress due to reactive oxygen species (Mischitelli et al, 2016). This deformation effect is likely to be due to the continuous exposure of diesel exhaust particles which alter the lipid bilayer.…”
Section: Discussionmentioning
confidence: 69%
“…Examples are provided by treatment of erythrocytes with the CDC25B phosphatase inhibitor NSC-95397 [35], the PLK1 kinase inhibitor BI-2536 [89], the protease inhibitor Lopinavir [22], the marine sponge-derived Fascaplycin [44], the selective histamine H1 receptor antagonist Terfenadine [58] and Fucoxanthin (a carotenoid from the chloroplasts of brown seaweeds) [25]. In parallel examples of substances interfering with eryptosis signalling, such as caspase inhibitor Z-VAD-FMK, p38 inhibitor SB203580, protein kinase C inhibitor staurosporine and casein kinase 1 CK1α inhibitor D4476 [9] are provided.…”
Section: Introductionmentioning
confidence: 99%
“…Fascaplysin is a fused benzoyl-linked β-carboline alkaloid first obtained from the marine sponge Fascaplysinopsis bergquist near the Fiji islands in 1988 . Fascaplysin can inhibit cyclin-dependent kinase 4 to prevent ovarian cancer cell proliferation and metastasis and can increase suicidal erythrocyte death. Moreover, fascaplysin was reported to inhibit AChE with IC 50 around 1.5 μM, suggesting that this compound might be used to treat AD . Recently, it was reported that fascaplysin could preferentially prevent Aβ aggregation and protect against Aβ oligomer-induced neuronal death .…”
Section: Introductionmentioning
confidence: 99%